Optimization of Traffic Public Education by the Security and Safety Unit in Preventing Traffic Violations in Jepara Resort Police Area (Indonesian Journal of Police Studies, 2024)
The high number of traffic violations in the Jepara Regency area is a matter that needs to be considered and handled by the Jepara Resort Police where this can hamper the activities of the Jepara Regency community such as congestion and can even result in traffic accidents. The main cause of the high number of traffic violations by motorized vehicle drivers is the lack of public awareness of traffic rules. The type of research carried out by the writer in Jepara Regency was in the form of field research using a qualitative approach to the research implementation. The focus of the research is Optimization the implementation of Traffic Public Education by the Security and Safety Unit of Jepara Resort Police in order to prevent traffic violations as an effort to realize the Kamseltibcar Lantas. Data collection techniques used include interviews, observation and observation of documents. Data analysis techniques carried out in the form of data reduction, data presentation and drawing conclusions. Based on the results of research by the author it was found that the lack of public awareness of traffic rules was caused by the lack of understanding of the people of Jepara Regency about orderly traffic so that in order to reduce the number of traffic violations, the Security and Safety Uniti of Jepara Resort Police carried out Traffic Public Education as a preemptive effort, where the purpose of carrying out Traffic Public Education activities to provide education to the community regarding good and correct xvii traffic rules and to instill public awareness of traffic rules as an effort to prevent traffic violations by the people of Jepara Regency. However, in the implementation of Traffic Public Education there are still some deficiencies that can become obstacles in raising public awareness of traffic rules. Therefore it is necessary to solve the problem and the right solution in preventing traffic violations in order to realize direct traffic control in the Jepara Police area.
Keywords: Optimalisasi, Dikmas, Pelanggaran, Lalu Lintas, Kendaraan, Kamsel